The Effect of Value Clarification and Locus of Control Learning on Students' Moral Development Level - Sukisno Sukisno; Supiana Dian Nurtjahyani (AL-ISHLAH: Jurnal Pendidikan, 2024)
Moral education aims to enhance the ability to think morally and make ethical decisions by emphasizing methods of moral consideration and fostering recognition of value-based reasoning. This study investigates the influence of value clarification and locus of control on students' moral development. An experimental design was employed, using a questionnaire-based treatment to collect data from 150 students at Poltekes Surabaya and PGRI Ronggolawe University. Primary data was obtained directly from participants, ensuring reliability and relevance. Findings revealed that Value Clarification Learning significantly improves students' moral development, supported by a significance value exceeding 0.05. This method fosters active learning, encouraging students to integrate values into their daily lives. It also motivates learners to seek information and confidently express their opinions. The research demonstrates the effectiveness of Value Clarification Learning in promoting moral judgment, decision-making, self-value development, and respect for others. By actively engaging students, this method facilitates deeper moral understanding and practical application. Value Clarification Learning positively impacts students' moral development, highlighting its potential as a powerful educational strategy to enhance moral reasoning and ethical decision-making in higher education contexts. Future research should explore its application across diverse populations to generalize findings.